CREOLIZED TEXTS AS A MEANS OF DEVELOPING LINGUISTIC COMPETENCE OF STUDENTS WITH NON-LINGUISTIC SPECIALTIES - Rajabova Svetlana Mikhailovna (Ta’lim innovatsiyasi va integratsiyasi, 2026)
Abstract: The relevance of using creolized texts in foreign language teaching lies in the need to expand the content and teaching tools due to the limitless information capabilities of these materials. Currently, foreign language teaching methodologists do not deny the methodological potential of polycode texts, as they are an integral part of everyday life, thereby motivating students to study a foreign language. However, in modern methodological literature, there is a lack of practical recommendations for building a teaching system based on them. The purpose of this article is to evaluate the effectiveness of creolized texts as a means of developing linguistic competence in students majoring in non-linguistic specialties. The results of the study, obtained using descriptive statistics, indicate a moderate advantage of using creolized texts in developing lexical and grammatical skills in students majoring in non-linguistic specialties and the feasibility of using these types of texts in developing linguistic competence.